THE ROLE OF COMPUTER TECHNOLOGY IN STUDENTS' INDEPENDENT WORK - Nosirova Dilnurabonu Nodir qizi; Mahmudova Iroda Ismoilovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article discusses the didactic foundations of the use of computer technology in the process of learning a foreign language as a type of independent work of students. The main functions and advantages of using computer technologies as a means of managing students' independent work are noted, the main directions of improving the organization of independent work with their use are indicated.